Political contestation in policy implementation: A narrative inquiry into a needle exchange program. Issue 1 (2nd January 2023) - Miller, Hugh T.; Lofaro, Ryan
ABSTRACT: The policy literature increasingly recognizes the political dynamics in play during implementation, including participation and competition. Yet the complexity of policy contestation following enactment confounds scholars' efforts to generalize. Predictive generalization is not the end-goal of narrative inquiry, yet it a useful approach to the study of political competition. Using the Narrative Politics model to analyze a needle exchange program in Miami, Florida, this article portrays policy implementation as the interaction of the winning policy narrative (the enacted narrative) with managerial narratives that attempt to claim policy successes. Emergent policy narratives, as well as losing narratives remaining in circulation, may challenge that depiction. This article focuses on the evolution of policy narratives as the process moves from pre-enactment to implementation, thus highlighting the political contestation and enduring (or diminishing) fissures animating the discourse.